2021
DOI: 10.1038/s41698-021-00168-1
|View full text |Cite
|
Sign up to set email alerts
|

Patient-derived organoids as a predictive biomarker for treatment response in cancer patients

Abstract: Effective predictive biomarkers are needed to enable personalized medicine and increase treatment efficacy and survival for cancer patients, thereby reducing toxic side effects and treatment costs. Patient-derived organoids (PDOs) enable individualized tumour response testing. Since 2018, 17 publications have examined PDOs as a potential predictive biomarker in the treatment of cancer patients. We review and provide a pooled analysis of the results regarding the use of PDOs in individualized tumour response te… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

5
136
1
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 152 publications
(143 citation statements)
references
References 53 publications
(185 reference statements)
5
136
1
1
Order By: Relevance
“…As in other diseases like cancer, gerontologists are largely unable to predict treatment response for individual patients, resulting in patients receiving ineffective treatment with unnecessary exposure to toxic side effects and high treatment costs. Effective predictive biomarkers are needed to enable personalized medicine and increase survival for patients [ 73 ]. Personalized medicine strategies include protein-based, RNA-based, and genome-based stratification, though in oncology, precision medicine has been largely based on genomic biomarkers [ 74 ].…”
Section: Precision Medicine: Using Organoids Systems As a Tool To Screen Anti-aging Drugs/ Patient-specific Drug Testingmentioning
confidence: 99%
See 1 more Smart Citation
“…As in other diseases like cancer, gerontologists are largely unable to predict treatment response for individual patients, resulting in patients receiving ineffective treatment with unnecessary exposure to toxic side effects and high treatment costs. Effective predictive biomarkers are needed to enable personalized medicine and increase survival for patients [ 73 ]. Personalized medicine strategies include protein-based, RNA-based, and genome-based stratification, though in oncology, precision medicine has been largely based on genomic biomarkers [ 74 ].…”
Section: Precision Medicine: Using Organoids Systems As a Tool To Screen Anti-aging Drugs/ Patient-specific Drug Testingmentioning
confidence: 99%
“…A promising predictive biomarker is individualized tumor response testing using PDOs, in which anticancer agents are screened ex vivo on PDOs to predict the clinical response. PDOs represent a superior preclinical model system compared to previous models through their inherent heterogeneity, long-term stability, applicability for high throughput screens, and enhanced capacity to capture tumor characteristics [ 73 , 74 ].…”
Section: Precision Medicine: Using Organoids Systems As a Tool To Screen Anti-aging Drugs/ Patient-specific Drug Testingmentioning
confidence: 99%
“…They offer a valuable opportunity to screen for individualized therapeutic options, to test treatment efficacy in advance to setting up patient's therapeutic scheme and to analyze potential resistance mechanisms [65,66]. Therefore, PDOs may advance personalized medicine by predicting the clinical response of individual patients to antitumor agents.…”
Section: Organoids As An Enhanced Model For (Personalized) Drug Screeningmentioning
confidence: 99%
“…To generate an overview of the current evidence on transferability of cancer organoid treatment results to the clinical setting, Verduin et al and Wensink et al conducted (systematic) reviews on the predictive value of tumor organoids [66,99]. Wensink et al showed that 5 out of 17 studies included in their systematic review reported a statistically significant correlation and/or predictive value and 11/17 at least a trend for a correlation or predictive value [66]. Three studies did not find a relation between PDO and patients response and one study was unable to analyze this readout.…”
Section: Organoids As a Promising Tool For The Improvement Of Therapy Efficiency Predictionmentioning
confidence: 99%
“…As in other diseases like cancer, gerontologists are largely unable to predict treatment response for individual patients, resulting in patients receiving ineffective treatment with unnecessary exposure to toxic side effects and high treatment costs. Effective predictive biomarkers are needed to enable personalized medicine and increase survival for patients [73]. Personalized medicine strategies include protein-, RNA-based and genome-based stratification, though in oncology, precision medicine has been largely based on genomic biomarkers [74].…”
Section: Precision Medicine: Using Organoids Systems As a Tool To Screening Anti-aging Drugs/ Patient-specific Drug Testingmentioning
confidence: 99%